Real-time direct cell concentration and viability determination using a fully automated microfluidic platform for standalone process monitoring1. Issue 12 (21st June 2015) - Nunes, P. S.; Kjaerulff, S.; Dufva, M.; Mogensen, K. B.
<x xml:space="preserve">Abstract</x> Bioreactor process monitoring through cell-based assays using a high throughput automated microfluidic platform, implementing Dean vortices for sample mixing and dilution.